Combination of Household and Plant-Based Wastes as Natural Fertilizers for Rotifer (Brachionus sp.) Biomass Production - Irwan Ismail; Elen Marta Lutur; Ongen R. Lekirupy (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2026)
Rotifers (Brachionus sp.) are widely recognized as a crucial live feed in aquaculture hatcheries, particularly during the early larval stages of fish and shrimp. However, intensive rotifer culture still largely depends on commercial media and inorganic fertilizers, which are relatively costly and may pose environmental risks when used excessively. This study aimed to assess the potential of liquid organic fertilizer (LOF) derived from rice washing water and coconut water as an alternative medium to enhance rotifer biomass production. The experiment was conducted using a Completely Randomized Design (CRD) consisting of four treatments with three replicates, including three LOF concentrations (5, 10, and 15 mL/L) and a control treatment using commercial fertilizer KW21 (1 mL/L). The observed parameters included rotifer population density, specific growth rate (SGR), and water quality over a 10-day culture period. The results indicated that LOF application had a significant effect on rotifer population growth (ANOVA, p < 0.05). The highest population density and SGR were obtained at the 15 mL/L treatment; however, this treatment also exhibited a more rapid population decline during the later culture phase. In contrast, the 10 mL/L treatment showed a more stable growth pattern, maintaining relatively high population density until the end of the culture period, suggesting it as the optimal concentration. Water quality parameters remained within the tolerance range for rotifers (Brachionus sp.), indicating that differences in population growth were primarily influenced by nutrient availability rather than environmental conditions.In conclusion, liquid organic fertilizer based on rice washing water and coconut water demonstrates strong potential as a cost-effective, environmentally friendly, and sustainable alternative medium for rotifer culture, while also supporting the implementation of circular economy principles in aquaculture systems.